Politisasi Birokrasi Sebagai Tantangan Netralitas ASN Dalam Pemilu 2024 di Kota Medan - Annisah Putri; Varadilla Putri Shabanni (STISIPOL Raja Haji, 2026)
In the 2024 elections in Medan City, there is a politicization of the bureaucracy in the selection of presidential and vice-presidential candidates. There are issues in the 2024 elections in Medan City, such as one Civil Servant (ASN) who is not neutral in exercising their voting rights, showing a tendency towards bias before the elections by using certain symbols representing one of the candidates. Additionally, there is a high level of political interest in Medan City during the 2024 elections. The purpose of this research is to identify the factors causing the Politicization of Bureaucracy and efforts to achieve bureaucratic neutrality that occurred in the 2024 elections in Medan City. This research uses the New Institutionalism Theory. The method used in the research is descriptive qualitative, with data collection methods including observation, documentation, and interviews. The research results show that the politicization of the bureaucracy in Medan City during the 2024 elections is influenced by local political dynamics, lack of strict sanctions, and lack of public oversight. The government's efforts to achieve bureaucratic neutrality have been carried out through policies, education, and supervision, but challenges in implementation and law enforcement still need to be improved. It is hoped that the government and society will work together to create a more neutral and professional bureaucracy, so that public services can be provided without harmful political influence.